PEMIKIRAN FRIEDRICH NIETZSCHE TENTANG NIHILISME: IMPLIKASINYA TERHADAP MORALITAS MODERN - Febrianti Febrianti (ISSUE: Journal of Islamic Studies for Universal Dialogue, 2025)
This paper is a philosophical review of Friedrich Nietzsche’s thoughts on the concept of nihilism and its implications for modern morality. In Nietzsche’s view, nihilism emerges as a consequence of the “death of God,” which results in the collapse of traditional moral values that have been the basis of human life. This poses a great challenge for individuals and society to find new meaning in life. In his concept, Nietzsche distinguishes between passive nihilism, which is destructive, and active nihilism, which is creative as an effort to transvalue values. The research method used is a conceptual method with text analysis, a philosophical theory approach, and a qualitative research method to further understand Nietzsche’s thoughts on nihilism. This research found that Nietzsche’s nihilism not only implies criticism of traditional morality, but also offers an alternative to new morality through the idea of Übermensch. However, this concept still draws criticism, especially in its application to the modern context.